A study of micro finance institution’s role in developing the small scale enterprises of Ethiopia - Anubha Srivastava; Preeti Kulshresthra (Department of Management | Faculty of Economics and Business | Universitas Diponegoro, 2018)
This study was conducted in Gedio zone small scale enterprise financed by micro finance institution. The main objective the study was to evaluate and determine the factor that determines loan repayment performance of small scale enterprise financed by yirgachefeMFI. For the success of the study both primary and secondary data were collected to determine the loan repayment performance of small scale enterprises in Gedio zone. Questionnaire were administered to 50 borrower and manager of MFI. The data gathered are tabulated and interpreted for ease of analysis and suitability for the reader.